Exploring the Use of Formative Assessment in EFL Classroom: Teaching Practices and Challenges - Fourest Prapsetyana Satmawati (Proceedings Series on Social Sciences & Humanities, 2025)
According to the Regulation of the Minister of Education, Culture, Research, and Technology number 21 of 2022 concerning Education Assessment Standard, which is the basis for the Merdeka curriculum, formative and summative assessments are used to evaluate students' learning outcomes. Both play an essential role in assessing and supporting students, but they serve different purposes and occur at various times. Especially, in EFL classrooms where English is primarily learned in the class rather than in everyday speech, formative assessment plays a significant role in enhancing students' learning abilities. However, English teachers face difficulties and challenges in implementing formative assessment in the class. Therefore, this study deeply explores the phenomenon of implementing formative assessment in learning practices and the challenges faced. Data were obtained from classroom observation, interviews with an English teacher, and analysis of learning documents. An experienced English teacher who has been teaching for more than fifteen years at SMK YPE Sampang Cilacap regency was involved in this study. The finding reveals that teachers still often face difficulties conducting formative assessment in the classroom. There are two main reasons for these difficulties: time constraints and a lack of student response, because they feel embarrassed and afraid of being wrong in answering. For this reason, teachers must make simple formative assessments and utilize appropriate learning media. Teachers should be able to be students' best friends and create a classroom atmosphere that is fun to learn in. This needs to be mastered by all teachers, especially English teachers.